198k views
2 votes
Solve for x:
-12 = 1/2(6x - 12)

User Audra
by
4.5k points

1 Answer

5 votes

Answer:

x = -2

Explanation:

-12 = 1/2(6x - 12) Multiply everything inside the parentheses by 1/2

-12 =1/2(6x) - (1/2)(12)

-12 = 3x - 6 Add 6 to both sides of the equation

-6 = 3x Divide both sides by 3

-2 = x

Check:

Plug -2 in for x and see if statement is true

-12 = 1/2(6x - 12)

-12 = 1/2[(6)(-2) - 12] Simplify inside the brackets

-12 = 1/2(-12 -12)

-12 = 1/2 (-24)

-12 = -12

User Tim Hopper
by
6.4k points